Successful treatment of chronic hepatitis C in a hemodialysis - Milošević, Ivana; Karić, Uroš; Pešić-Pavlović, Ivana; Stevanović, Goran; Barać, Aleksandra; Smiljanić, Marijana; Arsenović, Aleksandra; Stevanović, Olja; Đonin-Nenezić, Miljana; Brmbolić, Branko (The Journal of Infection in Developing Countries, 2018)
We present the first case of successful direct acting antiviral therapy of chronic hepatitis C in a hemodialysis patient in Serbia. The patient infected with genotype 1a has been successfully treated with Paritaprevir/Ritonavir/Ombitasvir/Dasabuvir and Ribavirin. There are only a few real world reports regarding this therapeutic option in hemodialysis patients.